Simulation of the effects of dehydration and hyperhydration on running economy - Ler, H.; Thompson, M. W.; Ruell, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Elite athletes appear to drink a relatively small volume of fluid during prolonged severe exercise, culminating in a bodyweight deficit of 1-4% due to dehydration. While HR is known to be elevated when exercising in a dehydrated state, we know of no research linking dehydration with running economy (RE). Theoretically, the oxygen cost of running is related to bodyweight, and if bodyweight is reduced then ultimately RE should improve. Conversely, added weight (weight jacket with small sand bags) around the torso should increase the oxygen cost of running and HR. This study investigated the simulation of dehydration and hyperhydration on RE and the HR response to these conditions. Methods: Sixteen well trained male distance runners performed a control trial in a euhydrated state and undertook either 2 added weight (AW) trials (n=8; age: 44.3±4.2 yr; 71.1±6.0 kg; 174.3±6.9 cm; VO2max: 58.6±6.3mL/kg/min) or 2 dehydration (D) trials (n=8; 45.3±2.9 yr; 74.8±8.4 kg; 175.3±7.2 cm; VO2max: 58.2±6.6mL/kg/min). Each trial consisted of four different submaximal running speeds (65, 70, 75, 80% of VO2max; 4 min stages for each speed) on the treadmill in thermoneutral conditions (20°C; 40%rh). Hyperhydration was simulated with added weight to the torso which was equivalent to 3% (AW3) and 4% (AW4) BW while 3% (D3) and 4% (D4) BW deficit was induced via an exercise-heat exposure protocol. Expired respiratory gas samples were collected over the final 60s at each speed using the Douglas bag technique. Heart rate (HR) values were recorded within the final 15s of each speed of running. Results: Subjects were well hydrated prior to all AW and D trials with urine specific gravity <1.010. RE at each speed was expressed as both oxygen uptake (VO2, mL/kg/min) and caloric unit cost (CR, kcal/kg/km). VO2 significantly increased with speed (r=0.999; p<0.001); together with average CR (p=0.263) in all trials. No significant difference was found between D and AW trials in both VO2 (mL/kg/min) and CR (kcal/kg/km). HR increased linearly with each increment in speed for all trials and was significantly higher at 75 and 80% of VO2max in D3 and 65 to 80% of VO2max in D4 compared with AW3 and AW4 trials, respectively [(D3 vs. AW3: 147±5 vs. 140±5; 159±6 vs. 152±5); (D4 vs. AW4: 128±10 vs. 119±7; 140±8 vs. 129±6; 150±6 vs. 141±6, 161±5 vs. 152±5 bpm)] (p<0.05). Discussion: RE at speeds ranging from 65 to 80% of VO2max was not affected by 3-4% of bodyweight deficit or added weight. One possible explanation for these results is that when added weight is evenly distributed around the torso the additional oxygen cost is minimised and offset by an added contribution from the series and parallel elastic component of muscles and tendons at no metabolic cost.